A STRATEGIC FRAMEWORK FOR INTEGRATED GOVERNANCE, RISK, AND COMPLIANCE (GRC) AND SUSTAINABILITY AT TELKOM INDONESIA - Liza Mahavianti Syamsuri (Ikatan Dosen Menulis, 2025)
Integrating Governance, Risk, and Compliance (GRC) with Environmental, Social, and Governance (ESG) principles is crucial for large enterprises like Telkom to achieve sustainable growth and build stakeholder trust. Telkom has a solid foundation in both areas, with robust corporate governance, ISO 31000:2018-aligned risk management, and comprehensive compliance policies. Its